Capacidad emprendedora y desarrollo empresarial de las micro y pequeñas empresas de la ciudad de Iquitos 2022 - Mesia Chuquizuta, Athos Aecio (2022)
The general objective of the research was to determine the relationship between entrepreneurial capacity and business development of micro and small businesses in the city of Iquitos, 2022, then the study was of an applied type, descriptive-correlational level and non-experimental design. In addition, 100 micro and small entrepreneurs were taken as a sample, for data collection the survey technique and the questionnaire were used as an instrument. After processing the data in the Excel and SPSS programs, the work concluded that the entrepreneurial capacity is regular, due to the lack of criteria to analyze and evaluate the alternatives, generate new experiences, act on their own motivation and the encouragement of others, face the difficulties and obstacles along the way, lack of confidence in the ability of others, create opportunities for people to grow, develop and expand their capabilities. On the other hand, business development is classified as regular, since it rarely has an incentive plan, likewise, the strategies set have rarely allowed it to achieve its objectives, in addition, they rarely have the necessary technologies and, Lastly, agents of change have never made it possible to improve management. In summary, it is determined that the relationship between entrepreneurial capacity and business development in the mypes of the city of Iquitos is positive and considerable, since the rho correlation statistic showed a significance of 0.01 and a coefficient of 0.875.